Explainable GNN-Derived Structure-Property Relationships in Interstitial-Alloy Materials - Borge Durán, Ignacio (2024)
The properties of periodic solid-state materials are frequently modified by the inclusion of interstitial atoms deposited pseudo-randomly throughout the crystal lattice. Accurately calculating overall lattice properties currently requires time-intensive, high-level quantum (typically DFT) calculations, often on 1000s of stochastic lattices. ‘Interatomic potential models’ (IPM) can mitigate such computational burdens by awarding discrete coefficients to common interstitial geometric ensembles within the wider lattice, and then summing these in a simple regression. Human-designed IPMs however typically take years to be developed. Herein, using molybdenum carbide (Mo lattice, C interstitial added atom) as a model, we show a Crystal Graph Neural Network (CGNet) workflow that can derive near-perfect IPMs from <300 DFT inputs in seconds. We also report Crystal Graph Explainer (CGExplainer), which extracts the most important interstitial geometry ensembles, ranking them in terms of contribution to the target property as well, or better than human experts. Our pipeline (CGNet+CGExplainer) demonstrates high potential for generality in exploring lattice structure-property relations rapidly while maintaining accuracy and interpretability.